A Dangerous Awakening - Iheanyi M. Enwerem (IFRA-Nigeria, 1995)
Students of religion and interested observers of politics in Africa will cherish this book for providing a thorough analysis of the origin and politics of the Christian Association of Nigeria (CAN). A Dangerous Awakening chronicles the religious clashes in Nigeria, and shows how religion has been used in the struggle for political power. Dr. Enwerem bases his study on interviews and unpublished memos, papers and letters not otherwise accessible to the public. This book is an invaluable contri...